Trends in Milk & Dairy products consumption in 4th year MBBS students and assessing their bone densities - Humayun Mirza, Faheem Sabir, Faiza J. Tariq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Milk and dairy products provide a package of essential nutrients despite the established beneﬁts for bone health. Aim: To find trends in medical students of a senior class about their consumption of milk and the dairy products and measuring their bone densities, with dexa-scan, to assess risk of osteoporosis. Methodology: This cross sectional study was conducted online through Google classroom, in order to engage students and teachers for research activities and teaching methodologies at Lahore Medical & Dental College, Lahore, Pakistan for four months. After having detailed review of literature about the topic, we developed a simple structured questionnaire, which was uploaded to Google classroom assignment page and was kept ungraded form. Results: The pilot research group of 27 students were trained first online and then through the Google classroom collected the data from rest of the students of the same class. Data entry and cleaning was done through Google classroom. Descriptive statistics including frequency and percentage were used to represent the data. Data was analyzed statistically through Google Classroom Analyzer. Conclusion: Concluded from this study that the medical students who participated in this study were not taking the recommended daily amount of milk or dairy products. Recommendations: To achieve the recommended daily milk and dairy products serving consumption, family involvement recommended that specifically address support for promoting daily milk and dairy products intake among adolescents. Keywords: Milk, dietary habits, life style, medical students, online teaching, bone scan